2016
DOI: 10.3892/mmr.2016.5083
|View full text |Cite
|
Sign up to set email alerts
|

Nox4 has a crucial role in uric acid-induced oxidative stress and apoptosis in renal tubular cells

Abstract: Abstract. The purpose of the present study was to evaluate the effects of uric acid in promoting tubular cell apoptosis and verify the role of nicotinamide adenine dinucleotide phosphate oxidase 4 (Nox4)-induced oxidative stress in this process. HK-2 cells were used as a human proximal tubular cell model and co-cultured with various concentrations of uric acid with or without pre-treatment with the Nox4 inhibitor diphenylene iodonium (DPI). The apoptotic rate and the amount of reactive oxygen species (ROS) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…NOX-4 is the predominant form of NADPH oxidase in the kidney and is abundantly expressed as a source of ROS. It has been demonstrated that UA increases intracellular ROS production by activating NOX-4 in human tubular cells [ 34 ]. Thus, in this study, we investigated H 2 O 2 production in the serum and ROS production in the renal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…NOX-4 is the predominant form of NADPH oxidase in the kidney and is abundantly expressed as a source of ROS. It has been demonstrated that UA increases intracellular ROS production by activating NOX-4 in human tubular cells [ 34 ]. Thus, in this study, we investigated H 2 O 2 production in the serum and ROS production in the renal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It further suggested that Nox4 is the main source of ROS in response to high glucose [31], which may help develop novel effective therapeutic target to target Nox4 for treatment of diabetic nephrology. It was reported that the inhibition of Nox4 prevented uric acid-induced cell injury by suppressing phosphorylation of P38/ERK in HK-2 cells [13]. Thus, P38/ERK activation likely connects Nox4 with HK-2 cell apoptosis upon high glucose stimulations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the renal source of ROS mostly comes from NADPH oxidase (Nox), and inhibition of Nox by apocynin, a Nox inhibitor, has been proven to protect effectively against diabetic nephropathy [12]. Nox isoform Nox4 is most abundant in the tubule cells and its upregulation indicates renal tubular damage in diabetic nephropathy [13].…”
Section: Introductionmentioning
confidence: 99%
“…Potential mechanisms involved in the deleterious metabolic effects of uric acid (UA) include the ability of soluble uric acid to increase oxidative stress, mitochondrial and endoplasmic reticulum dysfunction, endothelial dysfunction, activation of the renin-angiotensin system, as well as increased synthesis and secretion of proinflammatory factors [ 2 4 ]. Depending on the cell type, UA may also cause increased proliferation (VSMC) [ 5 , 6 ] or apoptosis (renal tubular cells, endothelial cells) [ 7 , 8 ]. While UA is a prooxidant in the intracellular environment, uric acid may also function as an anti-oxidant and has been proposed to protect the central nervous system in conditions such as Parkinson’s disease [ 9 ]…”
Section: Introductionmentioning
confidence: 99%